Inductive logic programming : 25th International Conference, ILP 2015, Kyoto, Japan, August 20-22, 2015 : revised selected papers /: 25th International Conference, ILP 2015, Kyoto, Japan, August 20-22, 2015 : revised selected papers. (2016) - Unknown
No abstract available